(untitled) (The Peerian Journal, 2022)
The article examines the green instruments, problems and prospects of the green factor of economic growth in Uzbekistan, analyzes the international experience of transition to a green economy, and describes the main directions of development of the green economy in the Republic of Uzbekistan